Fear and Architecture Analytical study on Islamic religious buildings - Tayib, Abdullah; Amin, Khanda Mohammed (Sulaimani Journal for Engineering Sciences, 2015)
In terms of general aspect, this research examines the role of the fear factor in shaping architecture , and determine the relationship between fear and architecture and the impact on each other, this is done by determining the type of possible relationships between fear and architecture , identifying the sources of fear that formed the architecture , identifying moral and physical aspects of fear and its indicators in architecture , also to identify mechanisms that are a reaction aspects towards fear ( mechanisms to achieve security and safety ) . As for the specific aspect this research is studying the sense of fear in the Islamic religious buildings. The thesis addresses the relationship through two main sections , the first section of the study is the general concept of fear, and then study the relationship between fear and architecture by identifying types and levels of fear and its impact on architecture , while the second section of the thesis is to apply indicators concluded in hypothetical study on a range of selected local and international projects of mosques and shrines and then determine the final conclusions , which is the sense of fear ( fear and dread ) in Islamic religious buildings.
Keywords: Fear; Islamic buildings; psychological presence